"I Grew Up… I Was Still Small": Experiences before and after Juvenile Incarceration in South Africa. Issue 4 (7th August 2020) - Gagnon, Joseph Calvin; Murphy, Kristin M.; Howie, Sheryl M.
ABSTRACT: Child maltreatment and exposure to violence are pervasive in South African townships. Coupled with economic hardships, many youth turn to drugs and crime, and eventually come in contact with the juvenile justice system. The purpose of this study was to gain an in-depth understanding of how one young man perceives aspects of his life prior to, during, and after incarceration in South Africa. The study focuses on a semi-structured interview with "Bobby", a twenty-six-year-old male living in a city in western South Africa. The theoretical perspective guiding this study was Dilthey's hermeneutics. The interview data was analyzed using Gilligan's Listening Guide methodology. Prevalent themes include pervasive violence for Bobby at home and in school, drug abuse, gang activity, and crime. Bobby's experiences often produced dissonant melodic lines – conflicting voices that are in opposition with one another. Two voices of conflict were the voice of knowing his current reality and the voice of evading the violent reality that surrounds him. This study illustrates the need for research to hear the voices of other youth, as well as the need for research on effective school- and community-based interventions to address issues with the maltreatment of youth, substance abuse, and gang involvement.